Evaluación del rendimiento de un motor de cuatro tiempos, usando hidrógeno como combustible - Ortiz Sánchez, Daniel Fernando (2019)
The purpose of the research was to evaluate the performance of a four-stroke engine using hydrogen and gasoline as fuel. The experiment began by determining the number of generators that generated the optimum concentration of hydrogen, for which the types of electrolytes were made: sodium hydroxide, sodium bicarbonate, sodium chloride and potassium hydroxide. The construction of three generators is required and the amount of 0.10 kg of potassium hydroxide, five liters of water, is used as an electrolyte in a time of 300 days with a current of 8 A, to obtain the maximum concentration of 26,557 ppm of hydrogen. The variables in the study were: temperature, noise and fuel consumption of the engine. The results in terms of temperature have a maximum value of 105.6 ° C using gasoline and 81.7 ° C using hydrogen, so hydrogen presents 29.25% more efficiency than gasoline. The intensity of noise in the engine with the use of gasoline presented a maximum value of 98.7 dB compared to 85.7 dB of noise with the use of hydrogen, with hydrogen being the fuel 15.86% higher efficiency Finally the consumption of each fuel was evaluated, the engine and the petrol base consumed 0.51 l / min compared to 0.60 l / min of hydrogen, representing 14.72% of greater hydrogen consumption. Hydrogen has a higher octane rating and chemical volatility than gasoline.